Rancang Bangun Website Promosi Ekonomi Kreatif Menggunakan Metode RAD - Nugroho, Didin Dwi; Haq, Endi Sailul; Umam, Khoirul (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
This research discusses the design and development of a promotional website for the creative economy at the Department of Culture and Tourism of Banyuwangi Regency to address issues related to creative economy promotion and data collection. The aim of this study is to design a promotional website system for the creative economy that can effectively implement a website system, display dynamic data on the website, and ensure that users can easily navigate the website. The website design uses the Rapid Application Development (RAD) method. The scope of this research includes the focus on the design and testing of the website. The creative economy promotional website features main functionalities including a subsector menu, a creative economy registration menu, and a validation menu, and has been tested using the black-box testing method. The black-box testing results show that the system's functionality runs as expected. This conclusion indicates that the design and development of the creative economy website have successfully addressed the issues faced by the department and creative economy actors.